(untitled) (Ius Novum, 2022)
According to the well-established Supreme Court’s case law, the civil court is entitled to determine independently whether a tort constitutes a criminal offence even in the absence of a final judgement of conviction. This opinion was expressed by the Supreme Court for the purpose of applying the extended limitation period under Article 4421 § 2 of the Civil Code for claims for a tort that is a crime. The Supreme Court’s statement raises doubts on the grounds of the presumption of innocence. The purpose of this article is firstly to present the standard concerning the scope of the presumption of innocence in civil proceedings, created by the European Court of Human Rights on the basis of Article 6 § 2 of the ECHR, according to which everyone charged with a criminal offence shall be presumed innocent until proved guilty according to law. Then it is the assessment of the compatibility of the Supreme Court’s opinion through the perspective of the Convention standard.